A new model with old problems? - Rolf Hasse (Intereconomics, 1975)
The stabilization of export earnings from primary commodities within the framework of the Convention of Lomé was eulogized as a “historic event”, “a gleam of common sense in this world” and an approach to a general solution. How is this agreement to be judged?
Keywords: 330; Stabilization Fund Of Lomé